Repositioning the Bar and the Bench in quest for national development - Imam, Ibrahim; Egbewole, Abdulwahab Olasupo (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper investigates the contributions of the Bench (judges) and the Bar (Legal Practitioners) to development in Nigeria with particular emphasis on economic growth. The exploration is borne out of the mirage of challenges militating against implementation of development economic policies in the country and in particular is the incontestability of phenomenon of dispute, which inadvertently affects economic growth. In the realm of development, it is contended that the extent of judicial independence, complemented with a vibrant legal practitioner in the discharge of their respective constitutional responsibilities correlate with economic growth. In respect of the Bar, aside from representing clients in courts they contribute to economic growth and development through completing business and contractual obligations and commercial transactions, resolving disputes, facilitating the flow of funds and investments, encouraging innovation through the protection of intellectual property rights, and advising entrepreneurs on viable business solutions. Thus, a better and strong performing judiciary and lawyers without interference have shown to lead to more developed economy, associated with rapid growth of large, small, and medium businesses in the economy. While dispute is inevitable, in the sphere of economy, the right of contending parties to institute action or defend in courts as well as the right of the parties to be represented by legal practitioners makes the institution of the judiciary and the bar significant. This paper, which employs doctrinal research method, explores the constitutional mandates of the Bar and the Bench as agents of justice administration to determine the institutions contributions to development. The paper found that the Bar and the Bench have roles to play in propelling developmental economic strategies and implementations by making sure that due process and democratic norms are revered. It is concluded that for Bar and Bench to contribute to development there must be harmonious relationship between the without compromising justice.